Analyzing Business Strategies of a Company in Bangladesh by Comparing Three Rigorous Forecasting Techniques (Dhaka University Journal of Science, 2023)
Business organizations in Bangladesh are basically running their business through intuition based forecasting. But it is crucial to anticipate the near future as accurate as possible to make the business profitable. This helps the manager of a business organization to plan their resources properly and as a result the organization can minimize its cost and maximize profit. In this research paper, we will analyze the business strategies of a company in Bangladesh by comparing the results obtained from three different rigorous forecasting techniques such as Holt’s method, Holt-Winter’s method and Autoregressive Integrated Moving Average (ARIMA) method so that the business organization can select proper forecasting technique to run their business. For this, we will first illustrate and analyze basics of forecasting and time series analysis, usual forecasting methods, some rigorous methods e.g., Holt’s method, Winter’s method and Autoregressive Integrated Moving Average (ARIMA) models. We will carry out our analysis and calculation by using Microsoft Excel, statistical data analysis tool R and MATHEMATICA.Dhaka Univ. J. Sci. 71(1): 26-35, 2023 (Jan)